IMPLEMENTATION OF POLITICAL PARTY AS FACILITY OF POLITICS RECRUITMENT (Cadre Case Study at DPC PKB Sub-Province of Ponorogo) - Nia Rochmawaty; Sulton Sulton; Ambiro Puji Asmaroini (Universitas Muhammadiyah Ponorogo, 2017)
Target of this research was ( 1) Knowing model execution of cadre recruitmet exist in DPC PKB Sub-Province of Ponorogo ( 2) Knowing principle of recruitment cadre exist in DPC Party Evocation Nation Sub-Province of Ponorogo ( 3) Knowing the nature of party cadre rekrutmen executed by DPC Party of Kebangkitan Nasional Sub-Province of Ponorogo ( 4) Knowing band of recruitment party cadre did by DPC Party Evocation Nation Sub-Province of Ponorogo. This Research use method of descriptive qualitative this research was executed DPC PKB Sub-Province of Ponorogo, source of its data from 30 one who consist of cadre, member and official member of PAC and official member of DPC PKB Sub-Province of Ponorogo. This Research use interview method, triangulation and documentation. While data analysis use descriptive data analysis qualitative. Pursuant to research which had model cadre recruitmen at DPC PKB Sub-Province of Ponorogo use model of partisanship represent based rekrutmen of loyalitas and try to collect partisan with less is paying attention interest proved to wait its his in party come according to condition and rule of moment enlist in party. Principal of cadre recrutmen in DPC PKB according to regulation of government of no 11 year 2002 that is having to Indonesai Citizen (WNI), have never been punished prison, having education, skilled, membership, well-behaved, healthy spirit and bodily, did not pursuant to faction, race and also religion. While nature of its it DPC PKB Ponorogo have the nature of open according to AD / CHAPTER art of IV Section 5 that national party, democratic, and open whoever may become cadre, member as according to existing order. band of Rekrutmen cadre exist in DPC PKB Sub-Province of Ponorogo use coalition band and band of kaderisasi to recruit member cadre through training process and construction.